Analysis of borehole geophysical data from the Mora area of the Siljan Ring impact structure, central Sweden - Muhamad, H.; Juhlin, Christopher; Lehnert, O.; Meinhold, G.; Andersson, M.; Garcia Juanatey, M.; Malehmir, A. (Elsevier, 2015)
The Siljan impact structure is the largest known impact structure in Europe, the result of a Late Devonian meteorite impact (380.9 ± 4.6 Ma). It is outlined mainly by a ring of lakes and Palaeozoic sedimentary rocks of Ordovician to Devonian age. The Palaeozoic successions are generally poorly exposed, but often well preserved with clear stratigraphy. At some locations they are strongly tectonised with sharply inclined or nearly overturned packages of crystalline basement and/or sediments. Down-hole logging data were acquired in the western part of the Siljan impact structure to determine some of the physical properties of the Palaeozoic sedimentary rocks in the area. Boreholes Mora 001 (356 m logged depth), Vattumyra Production (420 m logged depth), Mora VM 2 (94 m logged depth) and Mobillyft (437 m logged depth) were logged for temperature, sonic velocity and electrical resistivity. Logging data were compared to the lithology in the Mora 001 core, which had been mapped in detail, and information from other cores in the area. Good agreement between the natural gamma log and the core lithology was found. The sonic log shows a marked difference in velocity for the more clastic Silurian succession compared to the Ordovician succession and the Precambrian basement. A synthetic seismogram shows that a high amplitude reflection is expected at the Silurian–Ordovician boundary, raising some questions concerning interpretation of a seismic profile located about 6–7 km north of the study area.Correlation of the borehole logs shows that the thickness of the Silurian succession varies rapidly in the area and that its composition differs over distances of less than 1 km. These rapid variations suggest that the study area may be located in a megablock zone that was highly influenced by the impact. Caledonian tectonics and changing depositional environments may also play a role in explaining the present-day borehole lithologies. Even though the boreholes are relatively far from the seismic profile and the geology is complex, the new data confirm that the Silurian has significant thickness along parts of the seismic profile. Potentially, the Silurian can be up to 450 m thick on parts of the profile. Further geophysical investigations in the area, including seismic surveying and gravity measurements, may help in mapping the complex structures away from the boreholes and discriminating between possible geological models.